2019
DOI: 10.4212/cjhp.v72i6.2945
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Clinical Decision Support Tool to Improve Antibiotic IV-to-Oral Conversion Rates at a Community Academic Hospital

Abstract: <p><strong>ABSTRACT</strong><br /><strong></strong></p><p><strong>Background:</strong> Antibiotic IV-to-oral (IV–PO) conversion is a key initiative of antimicrobial stewardship programs. Guidelines and education are commonly described interventions to promote IV–PO conversion; however, technological interventions may be more effective in changing practice. <br /><strong></strong></p><p><strong>Objective:</strong&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Eight studies significantly favored the CDS intervention 25,26,28,29,[31][32][33]35 ; 20% of the studies presented results that favored the CDS intervention without statistical significance 21,23,27 ; 13% of the studies favored the control groups 22,24 ; and 13% of the studies showed that the CDS interventions had no difference compared with the control group. 30,34 One study 24 favors pharmacists' check over CDS; however, this was explained by the authors that the CDS was self-developed and lacks a high level of specificity for drug-drug interactions (DDIs).…”
Section: Cds Intervention Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies significantly favored the CDS intervention 25,26,28,29,[31][32][33]35 ; 20% of the studies presented results that favored the CDS intervention without statistical significance 21,23,27 ; 13% of the studies favored the control groups 22,24 ; and 13% of the studies showed that the CDS interventions had no difference compared with the control group. 30,34 One study 24 favors pharmacists' check over CDS; however, this was explained by the authors that the CDS was self-developed and lacks a high level of specificity for drug-drug interactions (DDIs).…”
Section: Cds Intervention Analysismentioning
confidence: 99%
“…Of the 15 included studies, 5 were randomized controlled trials, 27,30,31,33,34 6 were quasi-experimental, 22,25,28,29,32,35 2 were observational, 23,26 and 2 were cohort studies. 21,24 All of the studies had a control group and all 15 studies were deemed as good quality using the Newcastle-Ottawa Scale.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations